Risk factors associated with physical and mental distress in people who report a COPD diagnosis: latent class analysis of 2016 behavioral risk factor surveillance system data - Stellefson, Michael; Paige, Samantha R; Barry, Adam E.; Wang, Min Qi; Apperson, Avery (My University, 2019)
Introduction: Challenges associated with COPD increase patients’ risk of physical immobility and emotional distress, perpetuating a cycle of symptomatic living that hinders patients’ self-management and adherence to a treatment regimen. There is limited evidence available on how discrete behavioral and health risk factors contribute to the physical and mental distress experienced by people living with COPD. Purpose: This secondary data analysis of 2016 Behavioral Risk Factor Surveillance System (BRFSS) sought to identify subgroups of people with COPD who were at the highest risk for physical and mental distress. Methods: We selected 16 relevant risk indicators in four health-related domains – 1) health risk behaviors, 2) lack of preventive vaccinations, 3) limited health care access, and 4) comorbidities – as predictors of physical and mental health-related quality of life (HRQoL) in the COPD population. Latent class modeling (LCM) was applied to understand how various health-related indicators in these four health domains influenced reports of physical and/or mental distress. Results: The majority of BRFSS respondents who reported a COPD diagnosis experienced physical (53.76%) and/or mental (58.23%) distress in the past 14 days. Frequent physical and mental distress were more common in females with COPD in the 45–64 years age group, who were also identified as white and in the lower socioeconomic group. Respondents with intermediate- to high-risk behaviors, intermediate to multiple comorbidities, limited access to health care, and intermediate to low use of preventive vaccinations were more likely to report frequent physical distress compared to the low-risk respondents. Similarly, respondents with high-risk behaviors, intermediate to multiple comorbidities, and low use of preventive vaccinations were more likely to report frequent mental distress than the low-risk group. Discussion: This analysis of updated 2016 BRFSS data identified high-risk Americans with COPD who could benefit from disease management and secondary/tertiary health promotion interventions that may improve HRQoL. Future research should address noted disparities in risk factors, particularly among low socioeconomic populations living with COPD.
Keywords: COPD, HRQoL, physical distress, mental distress, latent class modeling, BRFSS